Seasonal Onset Changes in Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The influence of calendar month, day length (photoperiod), and globar solar radiation (GSR) on onset of infantile spasms was reviewed retrospectively using records of 76 infants at the Hospital for Sick Children, University of Toronto, Ontario, Canada.